2021
DOI: 10.1177/00368504211029429
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of gene expression signature and diagnostic/prognostic biomarker identification of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers in the world. The landscape of HCC’s molecular alteration signature has been explored over the last few decades. Even so, more comprehensive research is still needed to improve understanding of tumorigenesis and progression of HCC, as well as to identify potential biomarkers for the malignancy. In this research, a comprehensive bioinformatics analysis was conducted based on the publicly available databases from both the Cancer Genome Atlas (TCGA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
4
5
0
Order By: Relevance
“…In the case of our study, TOP2A was also considered as a key or core gene for the progression and development of HCC. This finding was coincided with previous studies 12,14,15,18,[20][21][22][23][24][25]27,[32][33][34][35][36]39,[41][42][43]45,46,48,50,51,[54][55][56][57][58]61 .…”
Section: Discussionsupporting
confidence: 92%
“…In the case of our study, TOP2A was also considered as a key or core gene for the progression and development of HCC. This finding was coincided with previous studies 12,14,15,18,[20][21][22][23][24][25]27,[32][33][34][35][36]39,[41][42][43]45,46,48,50,51,[54][55][56][57][58]61 .…”
Section: Discussionsupporting
confidence: 92%
“…Twenty-five candidate cuproptosis-related genes expression were significantly unequal between tumor and normal liver tissues, and they were also significantly correlated with poor survival in HCCs. Previous studies have found that ABCB6 (34), CDKN2A (35), CDKN3 (36), and TPI1 (37) (catalyzing the conversion of dihydroxyacetone phosphate (DHAP) and D- ACO1, aconitase 1; ACP1, acid phosphatase 1; AOC1, amine oxidase copper containing 1; ATP6AP1, ATPase H+ transporting accessory protein 1; ATP7A, copper-transporting p-type adenosine triphosphatase 1; CI, confidence interval; CIAPIN1, cytokine induced apoptosis inhibitor 1; COA6, cytochrome c oxidase assembly factor 6; DLAT, dihydrolipoamide Sacetyltransferase; FDX1, ferredoxin 1; FDX2, ferredoxin 2; HR, hazard ratio; ISCA2, iron-sulfur cluster assembly 2; LIPT1, lipoyltransferase 1; MT-CO1, mitochondrially encoded cytochrome c oxidase I; MTF1, metal regulatory transcription factor 1; NDOR1, NADPH dependent diflavin oxidoreductase 1; NUBP2, nucleotide binding protein 2; PDHA1, pyruvate dehydrogenase E1 subunit alpha 1; SCO2, synthesis of cytochrome c oxidase 2; SLC25A3, solute carrier family 25 member 3; TMEM199, transmembrane protein 199; *P < 0.05; **P < 0.01; ***P < 0.001.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these datasets included 114 COAD samples processed on the GPL16694 Agilent-022522 SurePrint G3 CGH Array 4x180K (Probe Name Version) of GSE75500, which were applied as validation sets. Quality controls included relative expression (RLE) and standardized scale-free standard error (NUSE) implemented in the affyPLM package provided by Bioconductor ( Wang J et al, 2021 ) ( www.bioconductor.org ). Raw gene expression data were background corrected using the Robust Multi-Array Average (RMA) method, standardized using the Quantiles method, and summarized by the median polish method.…”
Section: Methodsmentioning
confidence: 99%